Anisotropy of Microstructure and Mechanical Properties in Low Carbon Steel Plates Additively Manufactured Using Gas Metal Arc Welding - Hassan Ali Saadawi; Adel M. Daw; Hesham R. Eshabani; Mohamed A. Saraj (African Journal of Advanced Pure and Applied Sciences, 2023)
In recent years, additive manufacturing (AM) for metals, which uses layer-by-layer deposition of materials to construct nearly net-shaped items, has attracted interest as a way to improve the effectiveness of production processes in a variety of industries. One of the latest developments in additive manufacturing techniques is Wire arc additive manufacturing (WAAM). In this work, a low carbon steel wall has been wire arc additively manufactured (WAAM) using the gas metal arc welding technique. an anisotropic behaviour of microstructure and mechanical properties such as impact toughness, yield strength, ultimate tensile strength, and the percentage of elongation have been investigated in three different directions, vertical (90°), horizontal (0°) and diagonal (45°). The pearlite fractions in Top, front and diagonal planes were 18.45%, 16.14% and 17.76% respectively. These variations of pearlite fraction affect the mechanical properties of the additively manufactured wall; the anisotropic percentages of ultimate tensile strength and impact toughness for the vertical and horizontal directions were 13.63 % and 9.42 % respectively, relatively higher than those of horizontal and diagonal directions.